Onychomycosis in Psoriatic Patients with Nail Disorders: Aetiological Agents and Immunosuppressive Therapy - Núbia Carvalho Pena de Oliveira Praeiro Alves; Tomaz de Aquino Moreira; Lucivânia Duarte Silva Malvino; José Joaquim Rodrigues; Roberto Ranza; Lúcio Borges de Araújo; Reginaldo dos Santos Pedroso (Hindawi Limited, 2020)
Psoriasis and psoriatic arthritis are chronic, relapsing, immune-based diseases. Psoriatic patients may have nail involvement in 50 to 80% of cases, and this may reach 85% in patients with joint disease, in spite of the fact that the relationship between psoriasis and onychomycosis is not well established. The aim of this study was to investigate the occurrence of onychomycosis in patients with nail disorders and diagnosis of psoriasis and psoriatic arthritis. This was a cross-sectional study in which 38 patients diagnosed with psoriasis and/or psoriatic arthritis were interviewed and had altered nail samples analysed by mycological and histopathological exams. Twenty-two (57.89%) patients had a confirmed diagnosis for onychomycosis. Seventeen (44.8%) had a positive direct mycological examination, 16 (42.1%) had positive cultures, and 12 (31.6%) were positive for fungi by histopathological examination. Dermatophytes were identified in nine (56.3%) cultures, and of these, eight were Trichophyton rubrum and one T. tonsurans. Yeasts were isolated in seven patients (43.75%), which included four Candida parapsilosis and three C. albicans. Six patients (15.78%) were not using immunosuppressive therapy, and the others were using methotrexate, etanercept, adalimumab, infliximab, secukinumab, or golimumab, in monotherapy or in combination with other drugs. The confirmed onychomycosis rate in patients using methotrexate alone was 92.8% (n = 13). We concluded that it is possible that there is a positive relationship between psoriatic disease and onychomycosis. And we highlight that it is also worth investigating in the future the possible role of immunosuppressive therapy (mainly methotrexate) as a predisposing factor for the development of fungal infections in psoriatic patients.